2021
DOI: 10.1016/j.brachy.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A novel combination of percutaneous stenting with iodine-125 seed implantation and chemotherapy for the treatment of pancreatic head cancer with obstructive jaundice

Abstract: Insertion of radioactive strips through the biliary stent has been reported to offer longer survival and patency than an uncovered conventional self-expanding metal stent in patients with unresectable malignant biliary obstruction. The aim of this study was to investigate the safety and effectiveness of intraluminal brachytherapy combined with 125 I seed implantation and transarterial infusion chemotherapy for the treatment of pancreatic head cancer with obstructive jaundice. METHOD: From October 2012 to Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In addition, the combination of percutaneous stenting with 125 I seed implantation and chemotherapy may bring remission of obstructive jaundice combined with an increased survival for obstructive jaundice treatment caused by unresectable pancreatic head cancer [ 25 ]. However, long-term efficacy of this treatment needs to be confirmed with further prospective studies [ 25 ]. CT-guided radioactive 125 I seeds implantation was the most reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the combination of percutaneous stenting with 125 I seed implantation and chemotherapy may bring remission of obstructive jaundice combined with an increased survival for obstructive jaundice treatment caused by unresectable pancreatic head cancer [ 25 ]. However, long-term efficacy of this treatment needs to be confirmed with further prospective studies [ 25 ]. CT-guided radioactive 125 I seeds implantation was the most reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, repair of the damaged epithelium was completed in approximately 60 days, and no significant radiological damage to the surrounding tissue was detected (15). Therefore, biliary intraparticle radiotherapy is safe and feasible, and many clinical studies have also confirmed its safety (6,8,14,16,17). Common adverse reactions of biliary seed implantation include biliary tract infection, pancreatitis, puncture tract bleeding, bile leakage, ascites leakage, and seed strand displacement, but few serious lifethreatening complications occur.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [19] investigated 50 patients with incurable pancreatic cancer subjected to intra-operative ultrasound-guided particle implantation, 26 of whom received GEM + albumin after particle and GEM + albumin paclitaxel chemotherapy again, with mOS of 14 and 11 months for patients who received and did not receive chemotherapy, respectively (p = 0.046). Chi et al [20] selected 21 patients with pancreatic head cancer accompanied by obstructive jaundice, all of whom underwent biliary stenting with 125 I particles combined with chemotherapy. The overall survival of these 21 patients was 5.2-23.3 months, which was similar to that of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Chi et al . [ 20 ] selected 21 patients with pancreatic head cancer accompanied by obstructive jaundice, all of whom underwent biliary stenting with 125 I particles combined with chemotherapy. The overall survival of these 21 patients was 5.2-23.3 months, which was similar to that of the present study.…”
Section: Discussionmentioning
confidence: 99%